Reduction of cost in castings by the method of radiographic test - Soundharya, T; V. Dhandapani, N (International Journal of Engineering and Technology, 2018)
Foundry in developing nations endures from low quality and low output due to the incidence of defects that may occupy single or multiple causes. Hence casting is a process of uncertainty. It is not an easy task, since casting is a complex process and has connections among various process and operations. Casting defects can negatively impact the bottom line of a foundry. Here an attempt is made cost cutback of castings in radiographic test. There are many defects which can be identified through radiographic test and these defects are reduced or remedied by means of welding. This study focuses about the cost reduction of castings by means of â€œTotal quality management toolsâ€.